The University of Toronto Concussion Symptom Scale: do initial symptoms predict outcome?. Issue 5 (11th March 2013) - Richards, Doug; Hutchison, Michael; Ekhtiari, Seper; Comper, Paul
Abstract : Objective: To explore symptoms during initial physician evaluation and time to return-to-play experienced by university level athletes. Design: Prospective case series of concussions during three athletic seasons (2009–2012). Setting: University of Toronto, Ontario, Canada. Subjects: Athletes who sustained concussions while involved in inter-university sports (practice or competition) in the following sports: volleyball, fencing, rugby, basketball, track, hockey, soccer, cheerleading, football, lacrosse, field hockey, and figure skating. A total of 85 concussions were reported from 68 athletes (37 males, 31 females) Intervention: David L. Macintosh Sport Medicine Clinic physicians documented athletes' post-concussion symptoms and recorded the date when a player was medically cleared to return to play. Main Outcome Measures: Symptoms as measured by the University of Toronto Concussion Symptom Scale (UTCSS) scores, time loss from competition, loss of consciousness, amnesia, and history of concussion. Results: 90.6% of athletes reported at least one symptom on the UTCSS at the first office-visit, with somatic symptoms most frequently reported. The average UTCSS score at 3 days following injury was 13.1 (range, 0–51), with female athletes reporting significantly more symptoms than males (p<0.01). Time loss was not significantly different between males and females. The only factor that predicted poor outcome (>14 days out) was endorsement of cognitive symptoms of the UTCSS (OR 1.30, 95% CI 1.03 to 1.68). Conclusions: Female athletes reported significantly more symptoms than male athletes following concussion. Cognitive symptoms of the UTCSS were significant predictors of time loss among university level athletes. Acknowledgements The authors wish to acknowledge the David L. Macintosh Sport Medicine Clinic, The University of Toronto Varsity Blues athletes, therapists, and support staff. Competing interests: None.